Degradation of Six Selected Ultraviolet Filters in Aquifer Materials Under Various Redox Conditions. Issue 4 (5th August 2013) - Liu, You‐Sheng; Ying, Guang‐Guo; Shareef, Ali; Kookana, Rai S.
Abstract Laboratory biodegradation batch studies were performed to investigate the degradation behavior of six selected UV filters, namely benzophenone‐3 (BP‐3), 3‐(4‐methylbenzylidene) camphor (4‐MBC), Octyl 4‐methoxycinnamate (OMC), Octocrylene (OC), 2‐(3‐t‐butyl‐2‐hydroxy‐5‐methylphenyl)‐5‐chloro benzotriazole (UV‐326), and 2‐(2'‐hydroxy‐5'‐octylphenyl)‐benzotriazole (UV‐329) in an aquifer microcosm (groundwater and aquifer sediment mixture) under aerobic and anaerobic (nitrate, sulfate, and Fe(III) reducing) conditions within 77 d. The results from the biodegradation experiments showed that the six UV filters were degraded well in the aquifer materials under different redox conditions. Rapid biodegradation was observed for BP‐3 and OMC in the aquifer materials, with their half‐lives of 1.5‐8.8 d and 1.3‐5.2 d, respectively. In most cases, aerobic conditions were more favorable for the degradation of the UV filters in aquifer materials. Relatively slow degradation of 4‐MBC, UV‐326, and UV‐329 under anaerobic conditions was noted with their half‐lives ranging between 47 d and 126 d, indicating potential persistence in anaerobic aquifers. The results showed that redox conditions could have significant effects on biodegradation of the UV filters in aquifers.